Promoting Cross-Cultural Competence Through Aesthetic Education Policy in a Selected University In Shijiazhuang, China - LUO, LINA (Pacific International Journal, 2025)
This study determined the extent to which school administrators promote the implementation of aesthetic education and its correlation with respondents’ cross-cultural competence (CCC). A comprehensive analysis was conducted, examining key areas including comprehensive development goals, classroom teaching, core subjects, and supplementary courses. The study’s findings indicate that school administrators effectively integrate aesthetic education across these areas, with particular strengths in assessment practices, professional development, and encouraging creativity. However, there are identified areas for improvement, such as enhancing student engagement and providing better support mechanisms for teachers. Demographic profiles of both teacher and student respondents were analyzed, revealing a significant representation of female educators and students. Additionally, the study found no significant differences in the perceptions of the promotion of aesthetic education based on sex, age, or length of service among respondents. The assessment of respondents’ cross-cultural competence was conducted across cognitive, affective, behavioral, and relational dimensions. The results show that respondents generally perceive themselves as competent in these areas, with room for improvement in fostering respect for all cultural backgrounds and emphasizing mutual respect. A significant positive correlation was found between the extent of school administrators’ promotion of aesthetic education and the overall cross-cultural competence of respondents. This finding underscores the critical role that aesthetic education plays in enhancing students’ abilities to understand, appreciate, and interact effectively with diverse cultures. The study concludes with recommendations to further integrate and promote aesthetic education, thereby fostering a more culturally competent and inclusive educational environment.